2018
DOI: 10.1186/s41984-018-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty with polymethyl methacrylate implant: solutions of pitfalls

Abstract: Background: Cranioplasty is important to cover defects following skull surgery and trauma for restoration of function and cosmoses. The objective of the study is to describe the author's technical experience with the use of polymethyl methacrylate (PMMA) implant for cranioplasty to achieve the best results and avoid complications. Methods: The author describes the indications, locations and operative techniques of cranioplasty using polymethyl methacrylate (PMMA) implant for 75 patients. The implant was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Regarding bone cement, our results are similar to the study done on 2003 (10) (11) . However, his study was conducted on patients with only small and medium sized defects (< 8cm).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding bone cement, our results are similar to the study done on 2003 (10) (11) . However, his study was conducted on patients with only small and medium sized defects (< 8cm).…”
Section: Methodssupporting
confidence: 90%
“…1-2 authors. (7,8,9,10,11) However, regarding complications, both groups Regarding titanium mesh, our results are similar to Honeybul et al, 2017 (7) who had only one patient (out of 31) with late infection who needed titanium mesh re-implantation after antibiotic course. Our results also agree with another study (8) which analyzed titanium mesh on 56 patients and found that an abscess developed in one patient (1.7%) who received high-dose steroids for 72 hours before reconstruction.…”
Section: Methodssupporting
confidence: 89%
“…In addition, the surgical duration is significantly increased and may lead to poor cosmetic outcomes in patients with large or complicated defects as the PMMA implant as in-situ molded during the surgery procedure. Furthermore, the heat generated due to the exothermic reactions or the release of toxic monomers intraoperatively can result in the focal tissue damage, which implicate local and systemic reactions [4,5]. Although this surgical operation may seem straightforward, the complications range from 15 to 41%.…”
Section: Introductionmentioning
confidence: 99%
“…All these properties are very important for preserving the high photocatalytic activity of the deposited photocatalysts. PMMA has also been used in biomedical applications due to its non-toxic properties, low cost, easy processability, compatibility and minimal inflammatory reactions with tissues, and greater fracture resistance, especially when used in cranioplasty [78][79][80]. It is also worth noting that PMMA is stable during photocatalysis and it is not decomposed by photogenerated electrons and holes or by reactive oxygen species created during photocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%